The Validity of the PICTS-SV and Its Effectiveness with Positive Impression Management: An Investigation in a Court-Mandated Substance Use Treatment Facility - Williams, Margot M. (Criminal justice and behavior, 2020)
Forensic practitioners are regularly called on to conduct highly consequential evaluations of risk for recidivism and violence. Accordingly, numerous specialized risk assessment measures have been developed to evaluate an array of relevant variables. As one conceptual approach, the Psychological Inventory of Criminal Thinking Styles (PICTS) assesses criminal thinking as a dynamic criminogenic need with predictive validity beyond historical factors. Because of its high reading level, however, a simplified version (PICTS-SV) was recently developed. The current investigation sought to (a) examine the two versions’ direct concurrence and (b) test the PICTS-SV’s vulnerability to risk minimization (RM). Two separate studies recruited 150 participants from a court-mandated substance use treatment facility. Study 1 established the PICTS-SV’s concurrent validity with the PICTS, especially at the composite level. Study 2 observed its robust resistance to RM distortion, although some validity scale revisions appear warranted. Overall, these results support the PICTS-SV’s utility for informing effective interventions and accurate risk determinations.